2021
DOI: 10.1111/jan.14912
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative systematic review on nurses’ experiences of workplace bullying and implications for nursing practice

Abstract: Workplace bullying within the nursing community is a global problem, which has spanned decades; it has detrimental effects on nurses and affects patient outcomes (Hartin et al., 2020;Trépanier et al., 2016). Several studies have revealed that nurses face greater risk of workplace bullying than other professions because of the nature of their job which involves high levels of human interaction daily (Waschgler et al., 2013). Furthermore, the stressful work environment contributes to an even higher probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 98 publications
0
32
0
Order By: Relevance
“…An appropriate investigation is mandatory, as is protection for those who report abuses. There must be space for a system, forums and safe space for open communication between employers and healthcare workers for follow-up regarding harassment or bullying within the healthcare organization [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate investigation is mandatory, as is protection for those who report abuses. There must be space for a system, forums and safe space for open communication between employers and healthcare workers for follow-up regarding harassment or bullying within the healthcare organization [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of many previous studies. For example, Shorey and Wong [ 15 ] reported that WPB negatively affects nurses’ physical and mental health; in addition, when a nurse becomes a target of WPB, their productivity and creativity decrease [ 15 , 16 ]. WPB’s adverse effect extended over patient safety [ 17 ] by decreasing the nurses’ competencies and quality of care, ultimately hindering the organization’s development [ 1 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The victims of workplace bullying exhibited varying responses to the event. Some surrendered to the bullying culture and displayed intention to leave, whereas others coped with, adapted to and even combated the bullying (Shorey & Wong, 2021). Furthermore, Kang and Yun (2016) reported that coping with the workplace bullying experience occurs through a four-phase process.…”
Section: Characteristics and Effects Of Workplace Bullying Interventi...mentioning
confidence: 99%
“…The American Nurses Association (2015) published a new statement on workplace bullying, in which it presented recommendations for primary, secondary and tertiary interventions for individual nurses and emphasized the organizations' responsibility to establish a zero‐tolerance policy towards incivility and bullying. Some essential measures include implementing and reinforcing a nursing code of ethics, implementing anti‐bullying policies within organizations and developing continuous management strategies (Shorey & Wong, 2021). Further, the Joint Commission (2021) announced an updated version of the Sentinel Event Alert that incorporates new workplace violence standards (effective as of January 2022).…”
Section: Introductionmentioning
confidence: 99%